ICT IN ENGLISH LANGUAGE TEACHING AND LEARNING (American Journal of Research in Humanities and Social Sciences, 2023)
This article defines that using of information and Communication technologies in english language ateaching and learning. Moreover, there are shown the result of using these technologies.